METHODS OF FINANCING OF INVESTMENT PROJECTS OF BIG STRUCTURES OF METALLURGICAL SECTOR - A. E. Nikiforov; L. M. Kravets; A. S. Vorozhun (Литьë и металлургия)
Instruments of attraction of the borrowed current assets for major structures of metallurgical branch are examined.